2023
DOI: 10.1039/d3cp01710a
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of multiple NO molecules on Au10and Au9Znplanar clusters. A comparative DFT study

Abstract: The doping of atomic clusters with transition metal atoms modifies to a lesser or greater extent the catalytic properties of pure specimens. Here we study by means of DFT the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…A similar theoretical study performed by Fernández and Balbá on multiple NO adsorptions on Au 10 − and Au 9 Zn − clusters found that after the first NO molecule is adsorbed, the subsequent adsorptions yield weaker adsorption energies. 140 This result means that a trade-off needs to be found where the adsorption strength is optimized with the amount of adsorbates on the surface. Additionally, different sized AuNPs are made up of different facets, which may yield different adsorption strengths and numbers of possible adsorbates.…”
Section: Issues To Be Tackledmentioning
confidence: 99%
“…A similar theoretical study performed by Fernández and Balbá on multiple NO adsorptions on Au 10 − and Au 9 Zn − clusters found that after the first NO molecule is adsorbed, the subsequent adsorptions yield weaker adsorption energies. 140 This result means that a trade-off needs to be found where the adsorption strength is optimized with the amount of adsorbates on the surface. Additionally, different sized AuNPs are made up of different facets, which may yield different adsorption strengths and numbers of possible adsorbates.…”
Section: Issues To Be Tackledmentioning
confidence: 99%